PENGARUH PENGENDALIAN TERHADAP EFEKTIVITAS PENERTIBAN IZIN USAHA PEMANFAATAN AIR BAWAH TANAH PROVINSI JAWA BARAT - Arianto, Febri; Rachmawati, Emi (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
The problem with this research is the inefficiency of the approval of underground water exploitation undertakings in the West Java Province. Based on the problem, the researchers formulate the problem as follows: How great is the impact of the control on the effectiveness of the issuance of underground water exploitation permits in the West Java province? In analyzing the problems studied, the author proposes the theory of control of Handoko (2003:359) while the theories of effectiveness of Duncan in Zulkarnain (2012:32). The hypothesis was formulated as follows: